Food and feeding of the ridgeback shrimp, Solenocera choprai Nataraj, along Karnataka coast - Dineshbabu, A P; Manissery, Joseph K (Indian Journal of Fisheries, 2011)
Though Solenocera choprai is an important shrimp resource from Karnataka coast, information on food and feeding of the species is lacking. ‘Index of preponderance’ method was used to study the food and feeding habit of the species. The food contents found were decapod crustaceans, unidentifiable mass, ‘fish remains’, molluscan shells, polychaete worms, sand, foraminiferans and small crustaceans (other than decapods) in the decreasing order of abundance. In adults, annual index of preponderance for decapod crustaceans, detritus and ‘fish remains’ were 43.82, 19.27 and 11.17 respectively. In females, the major component of the food was decapod crustaceans with indices above 40. Annual feeding intensity of adult S. choprai was 28.88% with the highest value of 54% observed in February and lowest value from June to December. The change in monthly feeding intensity of the species is found to be influenced by the disturbances in the sea bottom caused by upwelling. Feeding intensity was the highest in immature females (40.71%) followed by spent females.